2019
DOI: 10.4995/wrs.2019.11529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacement of alfalfa by big-leaf mulberry on growth performance, digestion and meat quality in growing rabbits

Abstract: <p>This study aimed to investigate the effect of sundried big-leaf mulberry (BLM) as a replacement for alfalfa on the growth performance, digestibility of nutrients, nitrogen (N) utilisation and meat quality in New Zealand White rabbits. One hundred and sixty weaned rabbits, aged 35±1 d and with a body weight of 755±26 g, were randomly assigned to the 4 treatments with 20 replicates of 2 rabbits (1 male and 1 female) each. Animal performance was evaluated between the 35th and 77th d of age in 40 animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…With the increase in the proportion of BP replacing silage maize, the average daily gain of goats increased significantly, and the feed utilization efficiency was significantly improved. Compared to silage maize, BP can provide more balanced amino acids to the goat and has a higher digestibility and utilization rate of high quality crude fibre (Li and Guo 2009;Wu et al 2019). The results showed that the replacement of silage maize by BP (30%) can promote growth.…”
Section: Growth Performancementioning
confidence: 99%
See 3 more Smart Citations
“…With the increase in the proportion of BP replacing silage maize, the average daily gain of goats increased significantly, and the feed utilization efficiency was significantly improved. Compared to silage maize, BP can provide more balanced amino acids to the goat and has a higher digestibility and utilization rate of high quality crude fibre (Li and Guo 2009;Wu et al 2019). The results showed that the replacement of silage maize by BP (30%) can promote growth.…”
Section: Growth Performancementioning
confidence: 99%
“…The higher the myoglobin content in muscle, the greater the red degree of meat colour (Li et al 2018). Wu et al (2019) found that the iron content of BP was higher than that of maize, and supplementation of BP had a positive effect on the red value of rabbit meat.…”
Section: Meat Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been widely used in feeding sheep, cows, pigs and so on. The leaves of paper mulberry contain 21.6% of crude protein and 4.3% of ether extract, both of which are higher than that of other forages [3].…”
Section: Introductionmentioning
confidence: 86%